Peran Lingkungan Sekolah dan Teman Sebaya dalam Pembentukan Karakter Peserta Didik di SD IT Permata Kita - Silvia Ningrum; Sartono Sartono (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Student character is an important aspect in forming a generation that is not only academically intelligent, but also has strong moral and social values. This study aims to examine the influence of the surrounding environment, especially the school environment and social interactions, on the formation of student character at SD IT Permata Kita. The results of observations and interviews with teachers show that a religious, educational, and positively cultural school environment is able to instill strong character values ​​such as politeness, tolerance, mutual respect, and responsibility. The school also actively runs a character development program through monthly studies and the Malam Bina Iman dan Takwa (MABIT) activity. However, the negative influence of peers remains a challenge that needs to be watched out for and managed. This article is expected to be a reflection material for educators and stakeholders in an effort to strengthen student character through a positive environmental approach.